Gastroesophageal reflux disease and autoimmune thyroiditis: features of pathomorphological manifestation in young people - Pasiieshvili, Tamara; Zhelezniakova, Natalia; Bocharova, Tetiana; Pasiyeshvili, Lyudmila (ScienceRise: Medical Science, 2021)
The aim of the work. To study the effect of concomitant autoimmune thyroiditis (AIT) on the pathomorphological features of lesions of the esophageal mucosa in young patients with gastroesophageal reflux disease (GERD). Material and research methods. The study included 165 individuals. The contingent of the surveyed was students of Kharkov higher educational institutions. The main group consisted of 120 patients with a combined course of GERD and AIT, the comparison group included 65 individuals with an isolated GERD. The morphological form of the GERD was revealed during esophagogastroduodenoscopy (“Fuginon” system). A histomorphological study of the obtained biopsy material from the mucous membrane of the esophagus was carried out. Samples were studied on an Olympus BX-41 microscope. Morphometric study of the esophageal mucosa was performed using the Olympus DP-Soft. Research results. Histological examination of biopsy specimens revealed that the main pathomorphological signs of GERD in both groups were hyperplasia of the basal zone, lengthening of epithelial papillae, leukocyte infiltration, intercellular edema, expansion of the intercellular space, dystrophic changes, submucous fibrosis, the presence of severe inflammatory infiltration in the submucosal layer. Presence of concomitant AIT was associated with a statistically higher frequency of occurrence of certain signs: hyperplasia of the basal layer of the epithelium, elongation of the papillae, epithelial edema, expansion of the intercellular space, dystrophic changes in the epithelium (p<0.05). Conclusions. The presence of concomitant AIT in young patients with GERD does not affect the incidence of erosive GERD, but is associated with a significant increase in the severity of erosive esophagitis. The comorbid course of GERD and AIT in the student population is accompanied by a significant increase in the incidence and statistically significant intensification of the severity of hyperplasia of the basal layer of the epithelium, elongation of connective tissue papillae and leukocyte infiltration compared with isolated GERD